A Review Of Shape And Size Considerations In Pinch Grips - Saptari, Adi; Poh, Kiat Ng (Taylor & Francis, 2014)
In handgrip-related studies,it has been theorised that modifying the design of object shapes and sizes to accommodate the hand can reduce risks of cumulative trauma disorders (CTDs).However,there appears to be a lack of theoretical groundwork to support this premise in the area of pinch grip research.Therefore,this article aims to provide a review of shape and size considerations in pinch grips.The literature reviews were first conducted individually on shape,size and pinch grip factors,followed by the development of a literature summary based on the theoretical connections among shape, size and pinch grips.Though further studies are still required,this review has provided fundamental knowledge on possible theoretical connections among shape,size and pinch grip factors.These preliminary efforts shed light on potential mechanisms that explain how shape and size can influence pinch grips towards preventing CTDs and maximising the human performance.